2006
DOI: 10.1038/sj.jhh.1002110
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between GNB3 C825T and ACE I/D polymorphisms in essential hypertension in Koreans

Abstract: Essential hypertension (EH) is considered a typical polygenic disease, so the evaluation of gene-gene interactions rather than the determination of single gene effects is crucial to understanding any genetic influences. The G-protein b3-subunit (GNB3) 825T allele, associated with enhanced G-protein signalling, is a strong candidate for interactions with polymorphisms, such as insertion/deletion (I/D) polymorphism of angiotensin I-converting enzyme (ACE) gene. We investigated whether there is an association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
28
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 42 publications
7
28
1
Order By: Relevance
“…3 As a result, RAS genes encoding for angiotensinogen (AGT), angiotensin type 1 receptor (AT1R) and angiotensin-converting enzyme (ACE) have been widely investigated in different ethnic populations. [4][5][6][7][8] In addition, recent studies have shown that the promoter variants of AGT gene significantly influence the rate of AGT transcription and plasma AGT. 9,10 Conflicting or even contradictory reports have been seen regarding the association between RAS gene polymorphisms and EH incidence, of EH.…”
Section: Firstmentioning
confidence: 99%
“…3 As a result, RAS genes encoding for angiotensinogen (AGT), angiotensin type 1 receptor (AT1R) and angiotensin-converting enzyme (ACE) have been widely investigated in different ethnic populations. [4][5][6][7][8] In addition, recent studies have shown that the promoter variants of AGT gene significantly influence the rate of AGT transcription and plasma AGT. 9,10 Conflicting or even contradictory reports have been seen regarding the association between RAS gene polymorphisms and EH incidence, of EH.…”
Section: Firstmentioning
confidence: 99%
“…The limitations of variable selection in LRs for testing SNP -SNP interactions have been widely discussed. 10,22,28,29 The primary limitation is the empty cell-effect that some genotype combinations have low frequency or zero responses. In an LR, two dummy parameters are usually needed for each SNP and more parameters are required for their interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies conducted in relation to genetic susceptibility to hypertension suggest that the AGT gene has relatively more consistent positive associations. 1,3 For example, Nakamura et al reported that the M235T genetic variant of the AGT gene was associated with an increased risk of hypertension in Japanese population, 4 but this association is not always observed in other ethnic populations, such as Australian Anglo-Celtic Caucasians or black AfroCaribbeans. Studies carried out on the ACE I/D polymorphisms are also conflicting-some show gender-specific associations, while others show that the D allele significantly increases the risk of hypertension in men of European and Japanese origin.…”
mentioning
confidence: 99%
“…Studies carried out on the ACE I/D polymorphisms are also conflicting-some show gender-specific associations, while others show that the D allele significantly increases the risk of hypertension in men of European and Japanese origin. 1,3 One pathway that has been associated with hypertension is the G-protein/signal transduction pathway system. Until recently, the C825T polymorphism in the b3-subunit of G-protein gene (GNB3) has been significantly linked with essential hypertension in Africans and Caucasians.…”
mentioning
confidence: 99%
See 1 more Smart Citation